Influence of Supply Chain Audit Quality on Audit Results through the Auditor's Ability in Detecting Corruption - Rahima Br. Purba; Erlina Erlina; Haryono Umar; Iskandar Muda (International Journal of Supply Chain Management, 2020)
This study examines the effect of supply chain audit quality on the quality of audit results through corruption detection. The object of this study is the auditor of the State Financial Examination Agency of the Republic of Indonesia, with the subject of the study being the state financial auditor. The respondents of this study were 99 state financial auditors. The results of the study revealed that audit quality, which has a positive effect on the supply chain audit quality results and corruption detection can mediate the effect of supply chain audit quality on audit quality results. This research has succeeded in defining clearly the difference between audit quality and the quality of audit results that so far, many academics and practitioners have confused about it.